Estratégias hidráulicas e divergências funcionais em espécies decíduas e sempre verdes da floresta tropical sazonalmente seca - Souza, Bruno Cruz de (2015)
Why the different species of angiosperms not are equally successful in all environments of planet? One recurrent explanation is based in concept of trade-off. It is understood trade-off per the negative relation between functional traits that cannot be optimized simultaneously by the plant. The variations in functional traits between plants are understood how adaptations of the species to environmental conditions in response at resource acquisition necessary for development. The hydric availability can be considerate the main environmental factor that affect almost all physiological and phenological processes of plants of direct and/or indirect form, therefore, modulating various trade-off. Our main goal is understand which hydraulic strategies and the physiology behavior in deciduous and evergreen species in response to drought. In first chapter, we analyzed the functional variation between deciduous and evergreen species for understand the divergence in the strategies of avoidance and tolerance to drought. We measured 17 leaf functional traits in 17 deciduous and five evergreen species. Furthermore, we measured the stomatal conductance (gs), photosynthetic rate based area and mass (Aarea/Amass) and the instantaneous and intrinsic water use efficient (WUEi and WUE) during the rainy season. We checked that the deciduous species exhibited bigger Amass, less leaf lifespan (LL) and leaf specific mass (LSM) when compared with evergreen species. Deciduous and evergreen species showed trade-off between drought tolerance and photosynthetic capacity, the bigger LF is the less the Amass. Although the deciduous species have showed larger Amass and gs than the evergreen species, we do not observed significant difference in WUEi and WUE. The difference in the strategies of drought avoidance and tolerance between deciduous and evergreen species are clearly observed indistinctly to hydric availability. In second chapter, we evaluated if are divergence or convergence in the hydraulic strategies in deciduous and evergreen species and how they respond to effects of the drought. We observed monthly the leaf phenology by relating with the vapor pressure deficit (VPD) and the soil water content (SWC). We performed monthly measurements of water potential predawn and related with the wood density (ρwood). We observed the variation in stomatal behavior and in daily water potential and lastly measurements and compared 17 leaf functional traits between the phenological groups. The separation of species in groups based only LF provides good understanding about hydraulic strategies in response to drought. Deciduous species exhibited different strategies (isohydric/anisohydric) independently of ρwood. Evergreen species do not exhibit difference of strategy, it is only anisohydric. We regard that hydraulic traits how the water potential gradient from roots to shoots (ΔΨplant), the water potential responsible for 50% of stomatal closure (ΨSC) and the difference in seasonal water potential (ΔΨseasonal) are key for identification of hydraulic strategies in species of the seasonally dry ecosystems.